2013
DOI: 10.1002/ajmg.a.36252
|View full text |Cite
|
Sign up to set email alerts
|

Cornelia de Lange individuals with new and recurrent SMC1A mutations enhance delineation of mutation repertoire and phenotypic spectrum

Abstract: We report on the clinical and molecular characterization of eight patients, one male and seven females, with clinical diagnosis of Cornelia de Lange syndrome (CdLS), who were found to carry distinct mutations of the SMC1A gene. Five of the eight mutations are novel, with two involving amino acid residues previously described as altered in a different way. The other three have been reported each in a single case. Comparison of pairs of individuals with the same mutation indicates only partial overlap of their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…Moreover, 33 larger deletions and one balanced translocation have been reported as well. A much smaller percentage of patients (~4-6%) have mutations in the cohesin complex gene SMC1A, [6][7][8] in which 34 mutations have been identified so far, 9 including missense mutations (82%) or in-frame deletions (18%). No frameshift or nonsense mutations have been reported in this gene, possibly because they are lethal or lead to a different yet unrecognisable phenotype.…”
Section: Mutational Spectrummentioning
confidence: 99%
“…Moreover, 33 larger deletions and one balanced translocation have been reported as well. A much smaller percentage of patients (~4-6%) have mutations in the cohesin complex gene SMC1A, [6][7][8] in which 34 mutations have been identified so far, 9 including missense mutations (82%) or in-frame deletions (18%). No frameshift or nonsense mutations have been reported in this gene, possibly because they are lethal or lead to a different yet unrecognisable phenotype.…”
Section: Mutational Spectrummentioning
confidence: 99%
“…6c): Smc1A residues K59, R62 and K149, and Smc3 residues H55, R61, K105, K106 and K157. In addition to the presence of Smc3-K105 and Smc3-K106, already involved in acetylation-regulated DNA binding 2, 32, 33, 38 , the presence of three additional amino acids in this group is noteworthy: Smc1A-K59 and Smc1A-R62, deletion of which has been related to CdLS 55, 59, 63 and Smc3-H55, mutation of which to Tyr has been associated with colorectal cancer 22, 54 .…”
Section: Resultsmentioning
confidence: 99%
“…5a and d). The variant residues Smc1A-N1166T and Smc3-Q1147E have been found in patients with CdLS 12, 55, 56 whereas mutated amino acids Smc3-D1143H and Smc3-A1148T have been related to acute myeloid leukaemia 21, 54 and colorectal cancer 54, 57 , respectively. The mutant Smc3-Q1147E was previously reported to potentially be involved in maintaining the dimerization contact between the Smc1A-head and Smc3-head domains 12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By direct sequencing of exon 9, we confirmed that this variant was present in the four affected sibs and in heterozygous form in the mother. The R469C mutation maps to the junction of the N-terminal coiled coil and the hinge, a region that is remarkably conserved 17 18. The PolyPhen (score=1)15 and SIFT (score=0)16 computer programs classify this missense mutation as damaging.…”
Section: Resultsmentioning
confidence: 99%